A survey on the use of games in Applied Behavior Analysis - Azoubel, Marcos Spector; Pergher, Nicolau Kuckartz (Perspectivas em Análise do Comportamento, 2017)
Games have been viewed as intervention instruments in different applied settings. e purpose of this study was to review research articles, published in Journal of Applied Behavior Analysis (JABA), that involved the use of games as an independent variable. Seventeen articles, published between 1968 and 2015, were selected. e most frequently manipulated elements were rules about how a game worked, the accumulation of points, and group consequences for individual responses. e majority of the studies were carried out in schools and focused on behaviors that were considered problematic. e results of these studies indicate the general effectiveness of games in behavior modification. The definition of “game” and the apparent innovation of gamification are discussed.